Development of environmentally friendly biopreparations for preserving the sustainability of natural resources (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The article presents data on an innovative biopreparation containing humic complexes, mineral components and biologically active additives. It has been established that due to its unique composition, the biological product improves the agrophysical properties of the soil, including structural organization, water retention capacity and density stability. Special attention is paid to the mineral component of the biological product – amorphous silicon dioxide, which improves the structure and circulation of minerals in the soil.
Keywords: natural resources, ecology, biological product, soil, humidity, density, humic substances, silicon dioxide